Voluntary disclosure of financial information on the Internet. - Chua, Shuh Luan. (2008)
The study in this paper researches on the factors that affect voluntary Internet disclosure of financial information. Taking in account the fast-growing rise of the relatively new technology, known as the Internet, companies are increasingly using the Internet as a new communication medium to provide financial information. In this study, we have applied transaction cost economics theory to explain the motivation behind voluntary disclosure decisions.